2022
DOI: 10.25217/igcj.v5i2.3000
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress, Role Expectation Conflict, Co-Worker Support, and Work-Life Balance among Muslimah Scholars: A Study in the Indonesian Historical Women Political Movement Members

Abstract: Women ulama or Muslimah scholars are ordinary people who experience role conflicts, problems with co-worker support, and work-life imbalances which would cause stress in the workplace. Some pieces of literature have examined these issues; however, a study in a specific community like Muslimah scholars who are Indonesian Women's Ulama Conference members (KUPI) is still limited. This study examines the effect of role conflict, co-worker support, and work-life balance on work stress among Indonesian female Ulama.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Co-worker support refers to the perception of employees that their co-workers are willing and able to help them with their tasks and problems. Recent studies have shown that there is a positive relationship between role expectation conflict and work effort, as well as work quality [35,36]. Role expectation conflict may positively boost work effort by promoting a sense of responsibility, striving, and healthy competition among employees [37].…”
Section: Role Expectation Conflict Co-worker Supportmentioning
confidence: 99%
“…Co-worker support refers to the perception of employees that their co-workers are willing and able to help them with their tasks and problems. Recent studies have shown that there is a positive relationship between role expectation conflict and work effort, as well as work quality [35,36]. Role expectation conflict may positively boost work effort by promoting a sense of responsibility, striving, and healthy competition among employees [37].…”
Section: Role Expectation Conflict Co-worker Supportmentioning
confidence: 99%